Physicochemical parameters of Bakun Reservoir in Belaga, Sarawak, Malaysia 13 months after reaching full supply level - Ling, TY; Nyanti, L; Theresa, Muan; Jongkar, Grinang; Sim, Siong Fong; Aazani, Mujahid (UKM, 2016)
Determining the water quality of Bakun Reservoir 13 months after it operates at full supply level is crucial for better understanding of changes in the physicochemical parameters, which may enable the prediction of its effects on the survival of aquatic life in the reservoir. This study determined 13 physicochemical parameters at six stations within the reservoir at fixed depths. The results showed that the minimum 5 mg/L of dissolved oxygen (DO) required for sensitive aquatic organisms was recorded at 6 m depth. However, DO was not detectable at depths exceeding 7 m. The water was acidic at depths of more than 10 m. Turbidity and total suspended solids increased corresponding with depth. Inorganic nitrogen were predominantly in the form of ammonia-nitrogen, creating an unhealthy environment for aquatic life. Concentration of Chl-a was significantly higher at the subsurface water than 30 m depth in four out of six stations. The present study shows changes in water quality as compared to the pre-impounded period and 15 months after the filling phase, in particular, stratification of dissolved oxygen, thermocline conditions and alkalinity. The changes varied according to the distance from the dam and may have been influenced by existing land developments within the area such as the construction of the Murum Hydroelectric Dam, oil palm plantations and timber concessionares. Though the water quality might have deteriorated, further study is needed to determine if this condition will prolong.